Relationship between Sectors Shares and Economic Growth in Palestine - Alataweneh, Dr. Haroon Mohammed (IJRDO - Journal of Business Management, 2017)
This study estimates an econometric model that incorporates the linkages among agriculture, manufacturing, non-manufacturing, and service sectors using a vector error correction model for Palestine. Three co-integrating vectors confirm that the different sectors in the Palestinian economy moved together over the sample period, and for this reason, their growth rates are interdependent. But, in the short run, agriculture in Palestine seems to have a partial role as a driving force in the growth of other non-agricultural sectors. The results of improved quality of services and restructuring the banking indicate that the agricultural sector fully benefit from the development of the commerce and services sector and the presence of credit market constraints could not hamper growth of agricultural output in Palestine.